Frequency of Neuropathic Pain and its Effects on Rehabilitation Outcomes, Balance Function and Quality of Life among People with Traumatic Spinal Cord Injury - Muhammad Shoaib, Ammar Abdul Rahman, Shahnawaz, Hina Anwer, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Spinal cord injury (SCI) is the damage of the spinal cord from the foramen magnum to the cauda equina which happens because of coercion, incision or contusion. Objectives: The study's main objective is to find out how often people who have a severe spinal cord injury have neuropathic pain and how it affects their rehabilitation, balance, and quality of life. Material and methods: This descriptive study was conducted in Sheikh Zayed medical college, Rahim Yar Khan during 2020 to 2021. Most of the patients had started a SCI programme early on, including neurosurgeon and orthopaedic consults and therapy. The data were collected during the initial visit of the patients. Results: The data was collected from 162 patients. At-level pain was reported by 34% of those with neuropathic pain, whereas below-level pain was reported by 66% of those with neuropathic pain. In certain cases, neuropathic pain was characterised as both at and below a certain degree. Conclusion: It is concluded that Patients with traumatic SCI often experience a condition known as europathic pain. Patients' rehabilitation outcomes, balancing function, and general well-being may be impacted, as well as their general well-being.